Worship as a Moral Act: A Thematic Study of Islamic High School Students - Habiburrahman, Zaky; Nafi, Anushka Mardhiah Binti Mohd; Alias, Muhammad Firdaus Bin (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2023)
The attitude and personality of a person who understands religious teachings differ from those of someone who does not,has not yet, or lacks such understanding. This difference is reflected in their attitudes and actions in daily life. The level ofone’s worship can be influenced by the depth of their understanding of religious teachings. However, it is possible forsomeone with extensive religious knowledge to neglect acts of worship. This study aimed to determine the level of students’knowledge and practice of worship. A qualitative method with a case study approach was employed. Data were obtained fromfifteen informants through in-depth interviews selected using purposive sampling techniques. All informants were activestudents of Islamic senior high school. The interview results were analyzed thematically using NVivo 12 qualitative analysis software. The findings show that the forms of worship taught and practiced by students include prayer, fasting, zakat, and ablution (wudhu’). Students generally understand the meaning, requirements, and pillars of these acts of worship. However, their knowledge was found to be relatively weak, as most were unable to answer the questions given. Interestingly, the students’ worship practices were consistent and had become part of their daily habits. This indicates that their worship practices have developed into personality traits (moral actions) but remain weak in understanding (moral knowledge) and have not yet reached the level of awareness (moral feeling).